PENDIDIKAN KARAKTER BERBASIS PESANTREN: STUDI KASUS DI SMP PUNCAK DARUS SALAM PAMEKASAN - -, Fauzan (IAIN Kediri, 2015)
This article attempts to examine the implementation of pesantren-based character education with a locus ofÃ‚Â Junior High School Puncak Darus Salam located in Potoan, Palengaan, Pamekasan, Madura. In his analysis,the author uses a qualitative-phenomenological approach in which the data is based on the model of Miles andÃ‚Â Huberman by interpreting the data interactively and continouesly. This research found that the cultivationÃ‚Â of character education in SMP Puncak Darus Salam is the implementation of its vision and mission, which isÃ‚Â to generate generation with the QurÃ¢â‚¬â„¢an and Sunnah-based special characters. The success of the characterÃ‚Â education implemented at the school is mainly supported by the integration of the school and pesantrenÃ‚Â curriculum. This article will elaborate further the character education focusing on three aspects: affective,Ã‚Â cognitive, and psychomotor.Keywords: Pendidikan Karakter, Afektif, Kognitif, Psikomotorik